Protocolo de evaluación de fuentes y recursos informativos en la sociedad del conocimiento: propuestas, enfoques y tendencias - Ayuso García, M.ª Dolores; Martínez Navarro, Victoria (Revista General de Información y Documentación, 2005)
This work presents a study of the evaluation proposals of information sources published in Internet, carried out by both studious of the matter and scientific and academic institutions. The analysis of the proposals evolution, from the first pioneer until the nearest to our days, is complemented with their own pragmatic context with products like the Current Web Contents of the ISI or the thematic directories of evaluation agencies like Sosig. They settle down the master lines of a new owned evaluation protocol, that being heir of the methodological proposal of the ISI, is born with the intention of being a tool of quality and of added value to the reference services in Internet. Walking toward the normalization and systematizing of the sources and resources of information in the Net.